Maternal blood mitochondrial DNA copy number and placental abruption risk: results from a preliminary study - Williams, Michelle A. (2013)
Oxidative stress and impaired placental function – pathways implicated in the pathogenesis of placental abruption – have their origins extending to mitochondrial dysfunction. To the best of our knowledge, there are no published reports of associations of placental abruption with circulating mitochondrial DNA (mtDNA) copy number – a novel biomarker of systemic mitochondrial dysfunction. This pilot case-control study was comprised of 233 placental abruption cases and 238 non-abruption controls. Real-time quantitative polymerase chain reaction (PCR) was used to assess the relative copy number of mtDNA in maternal whole blood samples collected at delivery. Logistic regression procedures were used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI). There was some evidence of an increased odds of placental abruption with the highest quartile of mtDNA copy number (P for trend = 0.09) after controlling for confounders. The odds of placental abruption was elevated among women with higher mtDNA copy number (≥336.9) as compared with those with lower values (<336.9) (adjusted OR = 1.60; 95% CI 1.04-2.46). Women diagnosed with preeclampsia and with elevated mtDNA copy number had a dramatically increased odds of placental abruption as compared with normotensive women without elevated mtDNA copy number (adjusted OR = 6.66; 95% CI 2.58-17.16). Maternal mitochondrial dysfunction appears to be associated with placental abruption in the presence of preeclampsia. Replication in other studies, particularly prospective cohort studies and those that allow for tissue specific assessment of mitochondrial dysfunction (e.g., the placenta) are needed to further understand cellular and genomic biomarkers of normal and abnormal placental function.